Media Video Pembelajaran Berbasis Video Scribe Pada IPA Kelas V Sekolah Dasar - Rezaldi; I Made Citra Wibawa; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2022)
In its application, learning media has yet to be used optimally. In addition, the teacher also conveys the material only by lecturing. It will undoubtedly make it difficult for students to understand the learning material. This study aimed to develop video scribe-based learning videos for science subjects for fifth-grade elementary school students. This type of research is development research using the ADDIE model. ADDIE development model. The research subjects were one media expert, one material expert, and two practitioners. Methods of data collection using observation and questionnaires. The instrument used in collecting data is the rating scale. The technique used to analyze the information is descriptive qualitative and quantitative analysis. The research results are the results of the assessment given to the learning material experts, namely 4.75, so they get very good qualifications. The evaluation provided by learning media experts is 4.75, so they get very good qualifications. The assessment given by the teacher is 4.83, so the qualification is very good. It was concluded that Videoscibe-Based Video is valid and feasible to use in learning. This research implies that the Videosribe-based learning videos that have been developed can help students learn science.